Study of Grooved Warhead Structure on Performance of Warhead Fragment Distribution Pattern - Q Jing; T Zhou (International Journal of Multiphysics, 2018)
Fragment distribution pattern is a major factor for fragmentation warhead of medium diameter gun weapon, two different grooved warhead structures on the outer surface of warhead are proposed in this paper to improve warhead fragment distribution pattern. Experiments are performed to validate effectiveness of said efforts, and results show diamond-grooved warhead structure produces more fragment distribution density around warhead axis than parallel-grooved warhead structure, while keeping identical fragment projecting angle and dispersion angle. Finally, optimum depth on the surface of diamond-groove warhead structure is also obtained through experiments, showing impressive capability to withstand barrel gunpowder pressure more than 300 hundred million pascal per square meter.